Islam and media - Ishak, Mohd. Shuhaimi; Solihin, Sohirin Mohammad (Canadian Center of Science and Education, 2012)

(untitled)
The most important roles of the media are agenda-setting and representation. The media, particularly from the West, seems to feature Islam constantly in the negative light. The portrayal of the negative image of Islam takes place by constructing an image of Islam with terrorism, violence, extremism and antipathy to the West. A more recent phenomenon of Western media towards Islam is the fanning of ‘Islamophobia’ a form of concerted efforts directed to frighten the world of the hostility and enmity imposed by Islam. The Muslim world needs to respond to such striking negative representation of Islam. Contrary to what is generally perceived by the West, Islam in its real essence means ‘submission’ and ‘peace,’ a religion that calls for resignation to Allah and promotes and defends peace in the person. As much as the media can disrepute the general Muslim population and Islam, it can also restore and further inform the public of the true image of the religion. Thus, the primary aim of this paper is to explore the utilization of a variety of media to disseminate information and news to Muslims as well as non-Muslims on the true teachings of Islam. Through the media, the proper propagation and understanding of Islam can be enhanced by highlighting the universal values of the teachings of Islam. The media is a very important tool for effective communication and dissemination about Islam which the Muslim world could utilize.